The Dynamic Relationship between Natural Gas and Economic Growth: Evidence from Indonesia - Sinaga, Obsatar; Saudi, Mohd Haizam Mohd; Roespinoedji, Djoko; Razimi, Mohd Shahril Ahmad (International Journal of Energy Economics and Policy, 2019)
The aim of the current study is to examine the importance of natural gas energy utilization in influencing economic growth using time series data from 1980 to 2017 in Indonesia. In doing so, the current study has adopted the refined methodology of Auto-Regressive Distributed Lags (ARDL) bound testing approach to examine the dynamic relationship among natural gas and economic growth with amplified understanding of the critical association to support the course of economic planning and policy making. The results of ARDL bound testing approach confirm that capital, labor force and natural gas utilization are strong determinants of economic growth in Indonesia. Likewise, the outcomes affirm that natural gas utilization have a constructive and positive effect on economic growth in Indonesia which implies that the natural gas is the main source of economic growth in Indonesia in the long run and short run. Also, the results of variance decomposition method confirm a bi-directional causal relationship between economic growth, natural gas utilization, labor force and capital in Indonesia. Keywords: Natural gas utilization, economic growth, labor force, Indonesia. JEL Classifications: Q4, O1, O4 DOI: https://doi.org/10.32479/ijeep.7748